Anti HSV-2 activity of Peganum harmala (L.) and isolation of the active compound. (January 2018) - Benzekri, Roudaina; Bouslama, Lamjed; Papetti, Adele; Hammami, Majdi; Smaoui, Abderrazak; Limam, Ferid
Abstract: Genital herpes is a sexually transmitted disease caused by herpes simplex virus type 2 (HSV-2). Nucleoside analogues such as acyclovir (ACV) are the usual therapy for treating HSV infection. However, the overuse of this drug has led to the emergence of resistant strains. Therefore, the search for new alternative or complementary molecules to overcome this obstacle is needed. In this objective, Peganum harmala was investigated for its HSV-2 activity. The organic extracts of the different plant organs were evaluated for their cytotoxicity on Vero cells by the MTT test and anti HSV-2 activity by plaque reduction assay. Only the methanol seeds extract was active with a 50% inhibitory concentration (IC50 ) and a selectivity index (SI) of 161 and 13.2 μg/mL, respectively. In addition, the study of the antiviral mode of action revealed that this extract exerts a virucidal action both during the entry of viruses and the release of the newly formed virions, whereas no cell protection effect was observed. The active compound was isolated by bio-guided purification using thin layer chromatography (TLC) and identified by GC-MS and HPLC-DAD-ESI-MS n as harmine. The combination of harmine standard compound with ACV showed a combination index (CI) of 0.5 indicating that these two compounds have a synergic effect. This data suggests that harmine could be associated to ACV to improve the treatment of genital herpes essentially for the immunocompromised patients. Graphical abstract: Image 1 Highlights: Peganum harmala MeOH seed extract showed anti-HSV-2 activity. Peganum harmala MeOH seed extract exhibited a virucidal action. Harmine was identified as antiviral active compound. Harmine exerted a synergic effect with acyclovir.